SELF-ESTEEM DEVELOPMENT OF THE MAIN CHARACTER IN “ANDY NOYA KISAH HIDUPKU” - Indah Sari Lubis (Universitas Singaperbangsa Karawang, 2019)
Someone`s life journey and his sacrifice could be seen from one`s personality lens owned. It was also including the character`s personality in literary works in which it was reflected in the author`s biography. In this study, the problem of the research was formulated as “How is the self-esteem development of the main character, Andy Noya, portrayed in his biography entitled ANDY NOYA KISAH HIDUPKU which could influence his life-career. The purpose of the study was to identify the self-esteem development of the main character, Andy Noya is portrayed in his biography ANDY NOYA KISAH HIDUPKU which influenced his life-career, based on the theory of humanistic psychology Coopersmith. This type of research was a literature research using descriptive qualitative research design with the approach of psychology literature. The finding of this study indicated that the main character, Andy Noya experienced a low self-esteem within his childhood. However, the main character`s self-esteem changes into high (positive) after he was adult and it influenced his life-career then.